Longitudinal Trajectories of Asthma and Allergic Comorbidities in the Korean Childhood Asthma Study - Yoon, Jisun; Yang, Hyeon-Jong; Rhee, Eun Hee; Lee, Eun; Park, Ji Soo; Jung, Sungsu; Kim, Kyunghoon; Kim, Hwan Soo; Baek, Hey-Sung; Kim, Woo Kyung; Yoo, Young; Suh, Dong In; et al. (Allergy, asthma & immunology research, 2025)
Studies on the longitudinal clinical features of asthma or allergic comorbidities in children are limited. We aimed to examine the trajectories of asthma and allergic comorbidities and determine whether these trajectories differ according to clinical asthma phenotypes from birth to adolescence. We enrolled 958 children with physician-diagnosed asthma from the Korean childhood Asthma Study (KAS) cohort. Children with asthma were classified using hierarchical cluster analysis. Information on the diagnosis and treatment of allergic diseases before cohort entry was collected through linkage with national claims data from the Health Insurance Review and Assessment Service. In the KAS cohort, approximately half had a history of atopic dermatitis (AD) before infancy, with its prevalence gradually decreasing during adolescence. The prevalence of allergic rhinitis (AR) increased with age. The prevalence of asthma increased during early childhood and decreased during adolescence. According to the natural progression of asthma, AD, and AR trajectories, 4 distinctive phenotypes were identified using latent class analysis: "almost controlled," "early-onset asthma with AD and late-onset AR," "early-onset asthma only," and "intermediate-onset asthma and late-onset AR." Four distinct clinical trajectory patterns of asthma, AD, and AR were identified among the 4 cluster phenotypes based on baseline characteristics. Cluster 1 comprised male-dominant, atopic asthma with early-onset AD and late-onset AR. Cluster 2 included early-onset, atopic asthma with AD" persistent into adolescence. Cluster 3 encompassed "puberty-onset, female-dominant atopic asthma" with early-onset and low remission rates. Cluster 4 comprised "early-onset asthma with less atopic features" and the lowest comorbidities of AD and AR. The longitudinal trajectories of asthma and allergic comorbidities in Korean children can be classified into distinct clusters. Most phenotypes exhibited early-onset asthma with a varying prevalence of comorbidities. The persistence of AD, rather than its onset age, determines the phenotype.